(untitled) (Itinera, 2025)
The article investigates the aesthetic and theoretical implications of image production through generative algorithms, focusing on the short films Miss Polly Had a Dolly and THE PØRNØGRAPHƏR by HARIEL – Italian collective for AI Cinema as case studies. Drawing on Pietro Montani’s reflection on the syncretic nature of digital images (Immagini sincretiche. Leggere e scrivere in digitale, 2024), it examines how algorithmic images – bound to their verbal labels – exhibit a combinatory and self-referential creativity, a sign of an inert syncretism incapable of producing genuine semantic mediation. This condition is discussed in relation to Vilém Flusser’s theory and to the author’s necessity to “fight against the apparatus” in order to generate improbable, and thus truly informative, images. In analyzing the visual outcomes produced by text-to-video models, the essay demonstrates how hallucination acquire both aesthetic and cognitive value, becoming an instrument of resistance to the classificatory logics of artificial intelligence.